Emergence and Restraint: Indigenous Performances during the COVID-19 Pandemic - Wilch, Clara Margaret (Theatre Survey, 2021)
During the summer of 2020, I intended to make my second visit to Iqaluit, Nunavut, to speak with people involved in performance and climate science practices, engage in “co-performative witnessing” (methodology after Dwight Conquergood), and work to make my doctoral research useful to communities in Nunavut. 1 Needless to say, that didn't happen. However, the limitations imposed by COVID-19 have also been opportunities for all of us in performance studies to renew our understandings of what it is we do. The pandemic has forced me to understand my dissertation project differently and to reassess the complex process of respectfully engaging communities to which I do not personally belong.